(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Since ancient times, Madhya Pradesh has been a biodiverse region. The forests of Amarkantakare home to diverse vegetation,types in addition to natural habitats and this makes it one of the mostbeautiful places in central India. It is important to understand the importance of a biodiversity, Theuniqueness of different habitats and their flora and fauna make a rich ecosystem which needs to bepreserved for the future generation. Vegetation plays a vital role in the structure and function of anyecosystem. There are many factors, that limit the distribution of vegetation, like climate, soil, slope, andother factors. the globe is on the verge of catastrophic ecological collapse as a result of deforestation,habitat fragmentation, and human population expansion. Biodiversity conservation is a major priority forthe Achanakmar-Amarkantak Biosphere Reserve Thallophytes, bryophytes, pteridophytes,gymnosperms, and angiosperms are all represented in the Achanakmar-Amarkantak BiosphereReserve’s around 1498 plant species. A list of 184 plant species, including 24 pteridophytes and 160angiosperms, is presented in this article to highlight the ethnobotanical uses of the AchanakmarAmarkantak biosphere reserve’s indigenous peoples. The ethnobotanical applications of 90 kinds ofplants by the AchanakmarAmarkantak biosphere reserve’s tribal In .Tribal people in forests exercisewise use of plant resources and protect numerous plant species as a result. which has a long history ofrespect, care, and concern.This article focuses on various published papers, vegetational diversity inAmarkantak different types of forests, herbal medicines commonly used by local people in the treatmentof diseases.